2006
DOI: 10.1007/s11357-006-9015-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling psychomotor and cognitive aging in four-way cross mice

Abstract: In part due to their genetic uniformity and stable characteristics, inbred rodents or their F1 progeny are frequently used to study brain aging. However, it is recognized that focus on a single genotype could lead to generalizations about brain aging that might not apply to the species as a whole, or to the human population. As a potential alternative to uniform genotypes, genetically heterogeneous (HET) mice, produced by a four-way cross, were tested in the current study to determine if they exhibit age-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 53 publications
5
37
0
Order By: Relevance
“…Both tests are well-established behavioral testing paradigms for the assessment of learning and motor coordination in rodents, and mice specifically (Collier and Coleman 1991). Our results are in agreement with the findings for mice of similar age published by us and others previously (Collier and Coleman 1991;Dubey et al 1996;Forster et al 1996;Sumien et al 2004Sumien et al , 2006.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Both tests are well-established behavioral testing paradigms for the assessment of learning and motor coordination in rodents, and mice specifically (Collier and Coleman 1991). Our results are in agreement with the findings for mice of similar age published by us and others previously (Collier and Coleman 1991;Dubey et al 1996;Forster et al 1996;Sumien et al 2004Sumien et al , 2006.…”
Section: Discussionsupporting
confidence: 93%
“…The cortex and hippocampus are the primary brain regions involved in spatial learning and memory and responsible for swim maze test performance of rodents Forster et al 1996;Sumien et al 2004Sumien et al , 2006Nguyen 2006). Similarly, cortical and cerebellar networks are critical for motor learning and motor coordination (Hatsopoulos and Suminski 2011;Lamont and Weber 2012), as assessed in the present study by the bridge walking test.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The magnitude of the age-related impairments of psychomotor function observed in mice on the control diet in the current study was similar to that reported previously (Hengemihle et al 1999;Sumien et al 2004Sumien et al , 2006. The mice receiving the low or high dose of CoQ supplementation exhibited age-related deficits in performance, similar to the control group when tested for balance (bridge walking), coordinated running (rotorod), swimming, muscle strength (wire suspension), and spontaneous activity.…”
Section: Discussionsupporting
confidence: 89%
“…Spatial learning and memory were measured using a Morris water maze test as described previously (de Fiebre et al 2006;Sumien et al 2006). On a given trial, the mouse was allowed to swim in a 120-cm diameter plastic tank filled to 34 cm from the top edge with colored water (nontoxic white paint) and maintained at 24±1°C.…”
Section: Morris Water Mazementioning
confidence: 99%